Pengaruh Kebijakan Dividen Terhadap Abnormal return dengan Informasi Laba sebagai Variabel Pemoderasi - Ayyasyi, Alwan; Gurendrawati, Etty; Handarini, Dwi (Jurnal Ilmiah Wahana Akuntansi, 2022)
This research was conducted with the aim of knowing the effect of dividend policy on abnormal returns with earnings information as a moderating variable. The purposive sampling method was used as a sampling technique with 22 selected companies from 45 companies listed on the LQ45 index on the Indonesia Stock Exchange (IDX) from 2016 to 2020. This study used secondary data source obtained through the Mirae Asset Home Online Trading System software to obtain information related to dividends and share prices, and IDX website to obtain the publication of annual reports to obtain information related to company profits. The results of this study indicate that dividend policy has a negative effect on abnormal returns. Meanwhile, earnings information has not been able to moderate the effect of dividend policy on abnormal returns.